Philippine environmental law : comments and materials. (Quezon City, Philippines : The National Environmental Protection Council, 1983)
This book contains sectoral commentaries and for one who wants to inquire further into any environmental legislation, he may correspondingly refer to the list and text of legislations at the end of the commentary for each sector. It offers information background, fundamental principles and concepts, ideas to spark the imagination and foundations for the formulation of opinions on major environmental issues.
Presidential decree no. 1121 -- Presidential decree no. 1151 -- Presidential decree no. 1152 -- Presidential decree no. 1160 -- Presidential decree no. 1396 -- Presidential decree no. 1586 -- Letter of instruction 549 -- Letter of instruction 1179 -- Republic act no. 3720 -- Republic act no. 3931 -- Presidential decree no. 984 -- Republic act no. 6425 -- Presidential decree no. book four -- Presidential decree no. 600 -- Presidential decree no. 979 -- Presidential decree no. 881 -- Executive order no. 32 -- Presidential decree no. 825 -- Presidential decree no. 856 -- Letter of instruction no. 247 -- Presidential decree no. 79 -- Presidential decree no. 166 -- Presidential decree no. 803 -- Executive order no. 171 -- Execuive order no. 233 -- Letter of instruction no. 47 -- Presidential decree no. 280 -- Presidential decree no. 936 -- Presidential decree no. 1144 -- Administratice order no. 303 series 1976 -- Administratice order no. 311 series 1977 -- Administratice order no. 39 series 1979
Keywords: ENVIRONMENTAL LAW -- PHILIPPINES